A High-Efficiency and Reconfigurable Rectenna Array for Dynamic Output DC Power Control - Wang, Yuchao; Song, Yangkun; Zhang, Bohan; Chen, Shaonan; Chen, Qiang; Zhang, Cheng (Frontiers in Physics, 2022)
In this paper, an output power reconfigurable rectenna array is proposed for the first time to harvest RF energy. The proposed rectenna array can be used to capture abundant RF energy with high conversion efficiency in a wide range of input power levels and load impedance at 1.88 GHz, 2.35 GHz, 3.5 GHz, and 4.9 GHz simultaneously. And the output DC power of the proposed rectenna array can be changed exponentially by altering the on-off state of the switches located between the antenna and the rectifier. The measured result shows that the output power is linearly related to the numbers of the opened switches. Therefore, the proposed rectenna array can be flexibly applied to battery-free or low-power-needed devices according to their different power requirements.